Hard ticks (Acari, Ixodidae) of Croatia - Krcmar, Stjepan (ZooKeys, 2012)
The present paper is based on original and literature data. In Croatia the first studies on the occurrence of ixodid species were made about 80 years ago. The number of tick species recorded in Croatia considerably increased during the 1950s, 60s, 70s and 80s of the past century. A total of 21 species of hard tick belonging to 5 genera have been recorded in Croatia. Ixodes is the best represented genus, with seven species recorded. Haemaphysalis is represented by six species, followed by Rhipicephalus with four species. Dermacentor and Hyalomma are represented by two species each. The ticks were collected on 47 different host species. Eleven tick species were collected on Bos taurus and Ovis aries , followed by Capra hircus and Equus caballus with 8 species and Canis lupus familiaris with 6 species. On the remaining 42 host species one, two or three tick species were collected. The most widespread tick is Ixodes ricinus which was found on 25 different host species.